A large-scale evaluation of intraperson isotopic variation within human bone collagen and bioapatite. (July 2022) - Berg, Gregory E.; Chesson, Lesley A.; Yuryang, Jang; Youngsoon, Shin; Bartelink, Eric J.
Abstract: This study investigated intraperson skeletal (herein referred to as either "intraperson" or "intraskeletal") variation in stable isotope ratios for collagen (C and N) and bioapatite (C and O) extracted from five to six long bones from 27 modern individuals. The maximum intraperson variation observed for collagen was 0.78‰ for δ 13 Ccoll values and 1.12‰ for δ 15 Ncoll values, with a mean variation (± SD) of 0.33 ± 0.18‰ and 0.45 ± 0.27‰, respectively. For bioapatite, the maximum intraperson variation was 1.63‰ for δ 13 Cap values and 4.80‰ for δ 18 Oap values, with a mean variation (± SD) of 0.81 ± 0.32‰ and 1.00 ± 1.03‰, respectively. These results generally agree with previously reported data on intraskeletal isotopic variation. Using a two- and three-standard-deviations-from-the-mean model with analytical quality control data included, it is proposed that two bones with differing collagen δ 13 Ccoll values greater than 0.75‰ are probably from different individuals, and those that have differing values greater than 0.95‰ are from different individuals. Likewise, differing collagen δ 15 Ncoll values greater than 1.05‰ are probably different, and greater than 1.35‰ are different. For bioapatite, the proposed values change to 1.55‰ and 1.90‰ for δ 13 Cap, respectively; for δ 18 Oap values no limits were set due to the unexpectedly large variation found in the study population. We highly encourage researchers to use extreme caution when interpreting δ 18 O values from bone apatite. We also note that these parameters were evaluated on modern samples and therefore may not reflect intraperson variation in past societies. Finally, we demonstrate application of these interpretative limits to sort commingled human remains cases. Highlights: We established limits for forensically meaningful intraperson isotopic variation. Limits for bone collagen are 0.95‰ for δ 13 Ccoll and 1.35‰ for δ 15 Ncoll . The intraperson limit for bone bioapatite is 1.90‰ for δ 13 Cap . Oxygen isotope delta values are highly variable, and no limits are suggested. Intraperson limits can be used to potentially segregate commingled human remains.